Atrial Arrhythmias and Electroanatomical Remodeling in Patients With Left Ventricular Assist Devices. Issue 3 (8th March 2017) - Deshmukh, Amrish; Kim, Gene; Burke, Martin; Anyanwu, Emeka; Jeevanandam, Valluvan; Uriel, Nir; Tung, Roderick; Ozcan, Cevher
Abstract : Background: The incidence, predictors, and impact of atrial arrhythmias along with left atrial structural changes in patients with left ventricular assist devices (LVADs) remain undetermined. Methods and Results: All patients who underwent LVAD implantation from 2008 to 2015 at the University of Chicago Medical Center were included. Electronic medical records, electrocardiograms, echocardiograms, and cardiac electrical device interrogations were reviewed. The association of arrhythmias and clinical covariates with survival was evaluated by Kaplan–Meier and Cox proportional hazards analyses. A total of 331 patients were followed for a median of 330 days (range 0–2306 days). Mean age was 57.8±12.8 years, 256 participants (77.3%) were male, mean left ventricular ejection fraction was 20±6.6%, and 124 (37.5%) had ischemic cardiomyopathy. Atrial arrhythmias (53.8%) were highly prevalent and frequently coexisted before LVAD implantation: atrial fibrillation (AF) in 45.9%, atrial flutter in 13.9%, atrial tachycardia in 6.9%, and atrioventricular nodal reentrant tachycardia in 1.2%. New‐onset AF was documented in 14 patients (7.8% of patients without prior AF) after the first 30 days with an LVAD. Increasing age, renal insufficiency, and lung disease were predictors of new‐onset AF after LVAD implantation. Of patients with paroxysmal AF, 43% had no further AF after LVAD. Left atrial size and volume index improved with LVAD ( P <0.005). History of persistent AF, atrial tachycardia, ventricular arrhythmia, coronary artery bypass, and low albumin were associated with decreased survival. Conclusions: Atrial arrhythmias are significantly prevalent in patients who require LVAD and are associated with increased mortality; however, LVADs induce favorable atrial structural and electrical remodeling.